2019
DOI: 10.1200/jco.2019.37.27_suppl.284
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing technology for malnutrition screening and referrals to nutrition services.

Abstract: 284 Background: The incidence of disease-related malnutrition in oncology patients ranges from 40-80%. This is the highest of all hospital patient groups. Malnutrition is associated with decreased quality of life, increased healthcare costs and intolerance to treatment. Screening for nutrition risk is often lacking in outpatient settings. Electronic health records could be utilized to improve the delivery of validated nutrition screening tools such as the Malnutrition Screening Tool (MST) in outpatient oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A United Kingdom audit also found higher screening rates after the implementation of a hospital nutrition screening program 26 . Likewise, research from Australian and United States of America hospitals report increased Malnutrition Screening Tool completion after the implementation of electronic health records 20,27–31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A United Kingdom audit also found higher screening rates after the implementation of a hospital nutrition screening program 26 . Likewise, research from Australian and United States of America hospitals report increased Malnutrition Screening Tool completion after the implementation of electronic health records 20,27–31 …”
Section: Discussionmentioning
confidence: 99%
“…26 Likewise, research from Australian and United States of America hospitals report increased Malnutrition Screening Tool completion after the implementation of electronic health records. 20,[27][28][29][30][31] Malnutrition remains common in acute hospital settings. Student dietitians found that 33% of patients were at risk of malnutrition on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated similar or lower rates of uptake of BPA-triggered nutritional screeners, including a 29% referral rate for nutritional services of cancer patients and a 39% average pediatric nutritional counseling and assessment rate. 17,18 Given the very low intensity of the centralized training approach that we used before BPA activation, screening nearly half of eligible children over the subsequent 6 months may be viewed as a success.…”
Section: Discussion/practice Implicationsmentioning
confidence: 99%